Plant Aquaporins in Infection by and Immunity Against Pathogens – A Critical Review - Zhang, Liyuan; Chen, Lei; Dong, Hansong (Frontiers in Plant Science, 2019)
Plant aquaporins (AQPs) of the plasma membrane intrinsic protein (PIP) family face constant risk of hijack by pathogens aiming to infect plants. PIPs can also be involved in plant immunity against infection. This review will utilize two case studies to discuss biochemical and structural mechanisms that govern the functions of PIPs in the regulation of plant infection and immunity. The first example concerns the interaction between rice Oryza sativa and the bacterial blight pathogen Xanthomonas oryzae pv. oryzae (Xoo). To infect rice, Xoo uses the type III (T3) secretion system to secrete the proteic translocator Hpa1, and Hpa1 subsequently mediates the translocation of T3 effectors secreted by this system. Once shifted from bacteria into rice cells, effectors exert virulent or avirulent effects depending on the susceptibility of the rice varieties. The translocator function of Hpa1 requires cooperation with OsPIP1;3, the rice interactor of Hpa1. This role of OsPIP1;3 is related to regulatory models of effector translocation. The regulatory models have been proposed as, translocon-dependent delivery, translocon-independent pore formation, and effector endocytosis with membrane protein/lipid trafficking. The second case study includes the interaction of Hpa1 with the H2O2 transport channel AtPIP1;4, and the associated consequence for H2O2 signal transduction of immunity pathways in Arabidopsis thaliana, a non-host of Xoo. H2O2 is generated in the apoplast upon induction by a pathogen or microbial pattern. H2O2 from this source translocates quickly into Arabidopsis cells, where it interacts with pathways of intracellular immunity to confer plant resistance against diseases. To expedite H2O2 transport, AtPIP1;4 must adopt a specific conformation in a number of ways, including channel width extension through amino acid interactions and selectivity for H2O2 through amino acid protonation and tautomeric reactions. Both topics will reference relevant studies, conducted on other organisms and AQPs, to highlight possible mechanisms of T3 effector translocation currently under debate, and highlight the structural basis of AtPIP1;4 in H2O2 transport facilitated by gating and trafficking regulation.